Boiling Heat Transfer in Dilute Emulsions - Roesle, Matthew Lind. (SpringerBriefs in Thermal Engineering and Applied Science,, 2013)
Boiling Heat Transfer in Dilute Emulsions synthesizes recent advances and established understanding on the subject of boiling in dilute emulsions. Experimental results from various sources are collected and analyzed, including contemporary experiments that correlate visualization with heat transfer data. Published models of boiling heat transfer in dilute emulsions, and their implementation, are described and assessed against experimental data.